Emotional Intelligence Contributes to Increased Ranking in Combat Athletes with Anxiety Disorders - Aedo-Munoz, E (Editura Universitatii din Pitesti, 2022)
Considering the performance, this research associated emotional intelligence and anxiety between ranked and non-ranked combat sports fighters. Our research investigated 920 reports, of which 476 were excluded because they presented incomplete data; therefore, the last sample was collected of 444 data reports of ranked (n=235, age:23.5±7.5yrs.-old, time of practice: 15±7.3 yrs.; training/week:8.6±4.5 hours) and non-ranked (n=189, age:26.3±1. 2yrs.-old, time of practice: 1. 3±6.6 yrs.; training/week:4.6±2.5 hours) fighters from different combat modalities. The emotional Intelligence Scale and Trait Meta-Mood Scale were analyzed with Mann-Whitney, and logistic regression analysis showed the dependence amongst ranking and psychological factors, p≤.05. The main outcomes presented that non-ranked vs. ranked athletes were different in cognitive anxiety [62(35; 87) vs. 53.5(29.3; 75.8)], phobic anxiety [20(6; 41) vs. 14(4; 32)], total anxiety [122(69; 186.5) vs. 101.8(57; 164.8)] and self-regulation of emotional intelligence [27(22;32) vs. 30(25;33)]. The performance ranking model positively impacted emotional self-regulation and weekly training volume (Exp B – 1.420). Thus, coaches and fighters could develop psychological strategies, reducing cognitive and phobic anxiety and increasing emotional intelligence to improve the specific position in competition’s seeds and, consequently, rank. © 2022, Editura Universitatii din Pitesti. All rights reserved.